Tick salivary gland transcriptomics and proteomics. (16th November 2020) - Martins, Larissa Almeida; Bensaoud, Chaima; Kotál, Jan; Chmelař, Jindřich; Kotsyfakis, Michail
Abstract: 'Omics' technologies have facilitated the identification of hundreds to thousands of tick molecules that mediate tick feeding and play a role in the transmission of tick‐borne diseases. Deep sequencing methodologies have played a key role in this knowledge accumulation, profoundly facilitating the study of the biology of disease vectors lacking reference genomes. For example, the nucleotide sequences of the entire set of tick salivary effectors, the so‐called tick 'sialome', now contain at least one order of magnitude more transcript sequences compared to similar projects based on Sanger sequencing. Tick feeding is a complex and dynamic process, and while the dynamic 'sialome' is thought to mediate tick feeding success, exactly how transcriptome dynamics relate to tick‐host‐pathogen interactions is still largely unknown. The identification and, importantly, the functional analysis of the tick 'sialome' is expected to shed light on this 'black box'. This information will be crucial for developing strategies to block pathogen transmission, not only for anti‐tick vaccine development but also the discovery and development of new, pharmacologically active compounds for human diseases.